2002
DOI: 10.1038/sj.onc.1205794
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor activity of GW572016: a dual tyrosine kinase inhibitor blocks EGF activation of EGFR/erbB2 and downstream Erk1/2 and AKT pathways

Abstract: Dual EGFR/erbB2 inhibition is an attractive therapeutic strategy for epithelial tumors, as ligand-induced erbB2/EGFR heterodimerization triggers potent proliferative and survival signals. Here we show that a small molecule, GW572016, potently inhibits both EGFR and erbB2 tyrosine kinases leading to growth arrest and/or apoptosis in EGFR and erbB2-dependent tumor cell lines. GW572016 markedly reduced tyrosine phosphorylation of EGFR and erbB2, and inhibited activation of Erk1/2 and AKT, downstream effectors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
405
0
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 620 publications
(426 citation statements)
references
References 38 publications
14
405
0
6
Order By: Relevance
“…This is consistent with previous studies demonstrating that lapatinib treatment leads to the inhibition of EGFR and HER2, and consequently results in growth arrest and/or apoptosis in a variety of EGFR and HER2-dependent tumor cell lines (1,30). This is also concordant with the correlation between HER2 expression and the ability of lapatinib to inhibit HER2, Raf, Akt, and Erk phosphorylation in a panel of breast cancer cell lines (2).…”
Section: Discussionsupporting
confidence: 80%
“…This is consistent with previous studies demonstrating that lapatinib treatment leads to the inhibition of EGFR and HER2, and consequently results in growth arrest and/or apoptosis in a variety of EGFR and HER2-dependent tumor cell lines (1,30). This is also concordant with the correlation between HER2 expression and the ability of lapatinib to inhibit HER2, Raf, Akt, and Erk phosphorylation in a panel of breast cancer cell lines (2).…”
Section: Discussionsupporting
confidence: 80%
“…Other studies that considered cell lines in culture have shown that indeed not all tumor cells respond to inhibition of ErbB receptors, despite exhibiting aberrant EGFR and/or ErbB2 expression (Motoyama et al, 2002). In this respect, it has been reported that a combination of the EGFR-directed mAb C225 and the erbB2 directed mAb 4D5 or using dual EGFR/HER2 inhibitors inhibited proliferation of tumor cell lines more strongly than either mAb alone (Ye et al, 1999;Motoyama et al, 2002;Xia et al, 2002). A diagnostic protocol for predicting patient response to Herceptin and chemotherapy is presented in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were visualized using fluorescent-labeled secondary Abs and quantified by Odyssey Infrared Imaging System. These results are representative of three independent experiments xenografts (Rusnak et al, 2001;Xia et al, 2002). Although preliminary, GW572016 has shown antitumor activity in early-phase clinical trials in heavily pretreated subjects with metastatic cancers, notably breast cancer (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GW572016 inhibited p185 ErbB2 and p95 phosphorylation in S1 cells, a cell line established by single cell cloning of Hb4ac5.2 cells, a nonmalignant mammary epithelial line stably transfected with ErbB2 (Xia et al, 2002). In contrast, p95 was not identified in the EGFR-overexpressing head and neck squamous cell carcinoma line HN5 or in parental Hb4a cells, although exposure to 5 mM GW572016 inhibited phosphorylation of p170 EGFR (lower arrow) and p185 ErbB2 ,respectively (upper arrow).…”
Section: Resultsmentioning
confidence: 99%